Peran Dinas Koperasi Dan Usaha Mikro Dalam Pemberdayaan Usaha Mikro - Ainun Najib; Lailul Mursyidah (SOCIETAS, 2023)
Micro Business Actors (UM) are one of the pillars of the national economy. The Office of Cooperatives and Micro Enterprises has an important role in promoting micro enterprises. The role of the cooperative and micro business services is expected to create welfare and prosperity for micro business actors. The purpose of this study was to determine the role of the Office of Cooperatives and Micro Enterprises in empowering micro enterprises in Sidoarjo Regency. The research method used in this research is descriptive with a qualitative approach through interviews, observation and documentation and uses secondary data sourced from journals and books. The research location is at the Department of Cooperatives and Micro Enterprises (UM) Sidoarjo Regency. Based on the results of research on the role of the Office of Cooperatives and Micro Enterprises in empowering business actors as follows: 1) Facility Role; including the provision of Support, utilization of resources, and communication. 2) Educational Role; provide information related to punctured potency, and training. 3) Representative Role; includes cooperation in fostering and developing potential, opening networks with other parties, and obtaining venture capital. 4) Technical Roles; includes skills, management, and the ability to control finances.